(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Relations between Uzbekistan and the CIS, mutual exchange, historical and cultural dialogue were covered and analyzed on the basis of sources. Agreements have been made in the economic, social, political and cultural, scientific and educational fields. Further long-term plans have been identified.